How physicians draw satisfaction and overcome barriers in their practices: "It sustains me". Issue 12 (December 2017) - Branch, William T.; Weil, Amy B.; Gilligan, MaryAnn C.; Litzelman, Debra K.; Hafler, Janet P.; Plews-Ogan, Margaret; Rider, Elizabeth A.; Osterberg, Lars G.; Dunne, Dana; Derse, Arthur R.; Pittman, J. Richard; Frankel, Richard M.
Highlights: We studied what motivates or poses barriers to humanism. Strongest motivator was humanistic values embedded within professional identity. Barriers were time, stress, culture, and episodic burnout. Personal values were more highly developed than social role. Resolving the barriers requires partnering with others to address system issues. Abstract: Objective: Major reorganizations of medical practice today challenge physicians' ability to deliver compassionate care. We sought to understand how physicians who completed an intensive faculty development program in medical humanism sustain their humanistic practices. Methods: Program completers from 8 U.S. medical schools wrote reflections in answer to two open-ended questions addressing their personal motivations and the barriers that impeded their humanistic practice and teaching. Reflections were qualitatively analyzed using the constant comparative method. Results: Sixty-eight physicians (74% response rate) submitted reflections. Motivating factors included: 1) identification with humanistic values; 2) providing care that they or their family would want; 3) connecting to patients; 4) passing on values through role modelling; 5) being in the moment. Inhibiting factors included: 1) time, 2) stress, 3) culture, and 4) episodic burnout. Conclusions: Determination to live by one's values, embedded within a strong professional identity, allowed study participants to alleviate, but not resolve, the barriers. Collaborative action to address organizational impediments was endorsed but found to be lacking. Practice implications: Fostering fully mature professional development among physicians will require new skills and opportunities that reinforce time-honored values while simultaneously partnering with others to nurture, sustain and improve patient care by addressing system issues.